Pelatihan Penerapan Online Food Delivery (OFD) Sebagai Strategi Pemasaran Digital Usaha Mikro di Kedai Makan Dimsum Roda Berkah - Ricky Firmansyah; R. Dewi Sulastriningsih; Srie Wijaya Kesuma Dewi; Yunika Komalasari; Phitsa Mauliana; Nanang Hunaifi (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
One of the culinary businesses that is currently in great demand by the public in Greater Bandung is dimsum. Currently, dimsum is a ready-to-eat processed food that has been widely sold, from restaurants to street vendors. The development of market trends for dimsum products as well as public demand for practical food will encourage other entrepreneurs to take advantage of similar business opportunities. In today's modern era, with the rapid development of technology, people have to keep abreast of lifestyle changes such as consuming practical food, including how to order food through online food delivery (OFD). This community service activity is carried out to provide training on entrepreneurship, business strategy, OFD implementation, and strategies for dealing with competition between OFD users for the Roda Berkah Dimsum Sushi micro-business actor. The results of this activity are expected to have a positive influence, especially in increasing the business results undertaken by partners.